Case Study : Jean Paul Gaultier / Muhammad Ariff Firdaus Zali - Zali, Muhammad Ariff Firdaus (2021)
In performing this case study, the authenticity of purposes is to do some in-depth research on the chosen business. So, in this case study, I chose a well-known company that is renowned for its high-quality haute couture. There's nothing other than that, Jean Paul Gaultier. To be clear, before I chose Jean Paul Gaultier, I had done many studies on the history of the business, the founder, and so on. Jean Paul Gaultier has become one of the well-known fashion designer & business man, however his company also sell other products such as perfumes. In this case research, the study begins with a brief overview of the company, the business history, the business achievement or milestones, the personal background of the entrepreneur and also his personal achievements. In this case study, I had also included the entrepreneurial characteristics which focuses on the concern for self-confidence, efficiency orientation and also the use of influence strategies. Last but not least, the appendices I had inserted in the founder's photo, several product photos and collections of Jean Paul Gaultier Spring/Summer haute couture 2020 are also included.